Implementation of Interactive Learning Media on Citizenship Education Learning Motivation in the Digital Era - Nabila, Fidhlah Azkia (International Journal of Students Education, 2025)
This study aims to determine how students’ learning motivation is in the subject of Citizenship Education. This study uses a literature review method or library study by searching for relevant research results from several previous journals such as from the Google Scholar indexer, Sinta, Basicedu, and so on. Data collection techniques in this study include collecting library data, reading, and recording and processing research materials. The results of this study indicate that implementing Interactive Learning Media in Citizenship Education subjects in the digital era can increase the motivation and enthusiasm for learning of students both at elementary and secondary school levels. In addition, the use of Interactive Learning Media makes learning easier for both teachers and students. The use of Interactive Learning Media helps teachers to create creative learning videos so that students do not get bored quickly and find it easier to understand the material presented.